IMPLEMENTATION OF TERM DEPOSIT GUARANBINDING AT PT. BANK MANDIRI (PERSERO) TBK. MANDIRI PALEMBANG SUPPORT BRANCH OFFICE REGIONAL OFFICE II - Nurhayati, Ananda; Usman, Abdul Hamid; Hasyim, Yonani (PT. Altin Riset Publishing, 2024)
The purpose of this research is to determine the implementation of the binding of term deposit pledge guarantees on PT. Bank M Andiri (persero) T bk. Mandiri Palembang sub-branch office Regional Office I. This researcher used a juridical-empirical research methodology with literature studies and field studies, specifically through an approach to statutory regulations and other legal materials related to the problem as well as through observations and interviews with related parties, including related officials. credit agreement at PT. Bank Mandiri (Persero) Tbk. Mandiri KCP Palembang Regional Office II The results of this research indicate that the implementation of binding collateral for term deposits at PT. Bank Mandiri (Persero) Tbk. Mandiri KCP Palembang Regional Office II by implementing binding guarantees for term deposit pledges at PT. Bank Mandiri (Persero) Tbk. was carried out in five stages, namely the first stage by binding credit as the main agreement where it is stated that the credit guarantee is a deposit. The second stage, namely binding the deposit, is carried out by making a deed of pledge agreement between the deposit owner and the bank. The third stage is handing over the guaranteed deposit slip to the pawn holder, in this case, the bank. In the fourth stage, together with the third stage, the deposit owner or guarantor must authorize the pawn holder or bank to disburse the deposit in the event that the deposit owner or debtor defaults. In the fifth stage, the creditor, as the recipient of the deposit pledge, will block the collateral deposit in accordance with the terms of the credit agreement. This means that as long as the credit from the main agreement has not been repaid, the collateral deposit will be blocked.